Biomass ash reutilisation as an additive in the composting process of organic fraction of municipal solid waste. (November 2017) - Asquer, Carla; Cappai, Giovanna; De Gioannis, Giorgia; Muntoni, Aldo; Piredda, Martina; Spiga, Daniela
Highlights: A blend of boiler and fly ash is added to organic waste undergoing composting. The ash blend improves free airspace and organic matter degradation. The ash addition improves biostability and the humification of organic matter. The ash-amended composts are enriched in nutrients, in particular P and K. Biomass ash could be used as an additive in the organic waste composting. Abstract: In this work the effects of selected types of biomass ash on the composting process and final product quality were studied by conducting a 96-day long experiment where the source separated organic fraction of municipal waste, mixed with wood prunings that served as bulking agent, was added with 0%, 2%, 4% and 8% wt/wt of biomass ash. The evolution over time of the main process parameters was observed, and the final composts were characterised. On the basis of the results, both the composting process and the quality of the final product were improved by ash addition. Enhanced volatile solids reduction and biological stability (up to 32% and 52%, respectively, as compared to the unamended product) were attained when ash was added, since ash favored the aerobic degradation by acting as a physical conditioner. In the final products, higher humification of organic matter (expressed in terms of the humification index, that was 2.25 times higher in the most-enriched compost than in the unamended one) and total Ca, K, Mg and P content were observed when ash was used. The latter aspect may influence the composts marketability positively, particularly with regards to potassium and phosphorus. The heavy metals content, that is regarded as the main environmental disadvantage when using ash as a composting additive, did not negatively affect the final composts quality. However, some other controversial effects of ash, related to the moisture and temperature values attained during the process, pH (8.8–9.2 as compared to 8.2 of the unamended compost) and electrical conductivity levels (up to 53% higher as compared to the unamended compost) in the final composts, were also observed.